The Influence of Economic Growth, Population, and Industrial Sectors on Environmental Degradation in Indonesia - Rollis Juliansyah; T Zulham; Eddy Gunawan (Faculty of Economics, Universitas Sriwijaya, 2019)
Growth of the econonomic is the main problem of many developing countries (developing country) such as Indonesia itself, grasp with economic development as his instrument. It is in the form of environmental degradation that occurs as a by product that is not likely to attain many market participants even the Government though. On this simple research will be described in simple and concrete, where we restrict this research on variable environmental degradation in the form of proxy data CO2 emissions in Indonesia, economic growth, population, and industrial sectors. Whenever it is found to be the result of linear regression method with the double the result that environmental degradation occurs which by population growth and economic growth, each effect is positive and significant. However, the industrial sector showed a negative influence and significantly to degradation of the environment itself.